Spatial Variability of Salinity in Saline Soils - Thokal, R T; Gupta, S K; Chauhan, H S (Annals of Arid Zone, 2016)
This study addresses to a major problem experienced during leaching of saline soils, i.e., to quantify and estimate mean value of initial salinity of the soil. The. study was undertaken to test and recommend new options for studies related to spatial variability of soil salinity on the basis of flood frequency analysis procedures for estimating initial salinity to be used in various models of leaching. In describing the spatial variability of the soil electrical conductivity, classical statistical techniques have been used. The relative effectiveness of four transformations and five distributions has been reported. Although in the present study, Pearson type III distribution visually and logically should give the best results, yet it is observed that several options are statistically equivalent. It is also, brought that for leaching, EC at middle probabilities, i.e.; 3 confidence levels (50%, 80% and 90%) can be used to estimate initial salinity as per the strategies, instead of using the mean values.